Analisis faktor risiko yang berhubungan dengan nilai neutrophil lymphocyte ratio pada penderita tuberkulosis paru di Kota Semarang - Putri, Adita Puspitasari Swastya; Duri, Iin Desmiany; Afrianti, Dina; Negoro, Muhamad Syamsul Arif Setiyo (Poltekkes Kemenkes Aceh, 2025)
Background: The neutrophil-to-lymphocyte ratio (NLR) tends to increase in patients with tuberculosis (TB). The increase in NLR can also result from other risk factors, such as medical history, smoking status, treatment history, and treatment stage.Objectives: To determine the risk factors associated with the Neutrophil-to-Lymphocyte Ratio (NLR) in pulmonary tuberculosis patients in Semarang.Methods: This study used an analytical observational design with a cross-sectional approach. It was conducted at the Semarang Community Health Center from July 1, 2024, to August 31, 2024. The research sample consisted of pulmonary tuberculosis patients from five Puskesmas in the city, selected through cluster random sampling. Data were collected via laboratory test results and structured interviews. Descriptive analysis was used to evaluate frequency distributions, while bivariate analysis was used to assess relationships between variables.Results: Among 70 respondents, a significant relationship was found between treatment stage and the NLR in pulmonary tuberculosis patients at Kota Semarang (p=0,012). However, no significant relationship was found between comorbidities, smoking status, or treatment history and the NLR (p=0,525;0,790, and 0,525)Conclusion: The Neutrophil-to-Lymphocyte Ratio (NLR) decreased after patients progressed to the advanced treatment stage. Tuberculosis patients are encouraged to complete all stages of treatment and to stop smoking to enhance treatment outcomes.